Controlling the polymer ink's rheological properties and viscoelasticity to suppress satellite droplets. (28th February 2018) - Du, Zhonghui; Lin, Yangming; Xing, Rubo; Cao, Xinxiu; Yu, Xinhong; Han, Yanchun
Abstract: Stable and single droplet generation is essential in drop-on-demand (DOD) inkjet printing process to deposit homogeneous and flat film. However, polymer's rheological properties and viscoelasticity can influence filament break up and droplet formation, which may lead to the formation of satellite droplets. Controlling the Z constant (related to fluid viscosity, and surface tension) and Weissenberg (Wi) number can suppress the satellite droplets and get stable and single droplet. Here, mixed solvents (chloride benzene (CB) and high viscosity cyclohexylbenzene (ChB)), different molecular weight and concentration were employed to tune the polyfluorene (PFO) viscosity, surface tension and viscoelasticity. According to the droplet ink-jetting behavior of different CB/ChB ratio, PFO molecular weight and concentration, it's found that only when the speed of the secondary droplet is faster than that of the primary droplet, a single droplet could be formed. At last, we concluded that for PFO inks 9 ≤ Z ≤ 55, Re ≥ 3 and Wi = 0.5 were adequate judgement for a stable and single droplet formation and the two factors should be controlled simultaneously to ensure a stable and single droplet. Graphical abstract: Highlights: Adding high viscosity cosolvent ChB can decrease the Z constant and depress the satellite droplet. The speed difference variation (increased quickly and then decreased) was the reason for a single droplet formation. For PFO inks, 9 ≤ Z ≤ 55, Re ≥ 3 and Wi = 0.5 were adequate judgement to acquire a stable and single droplet.